Rehabilitation of school models in Lattakia using pushover analysis - سعيد, سعيد; أكرم صقور , (Latakia University Journal -Engineering Sciences Series, 2023)
Earthquakes in many parts of the world revealed weaknesses in existing facilities in these countries. The experience gained from observations and studies conducted on this topic has led to an increase in knowledge about seismic assessment. It is expected that structures will deform inflexibly when exposed to severe earthquakes, so the post-elastic behavior must be taken into account when evaluating the seismic performance of the structures, and therefore it is preferable to use nonlinear analysis procedures for the purpose of evaluation, because the behavior outside the elasticity field cannot be determined directly through elastic analysis. Furthermore, the inelastic seismic demand for the maximum transmission of the structure must be determined in order to make an adequate estimate of the expected seismic demand of the structure that manifests itself in the inelastic behavior. This research aims to study the effects of earthquakes on the existing schools in the city of Lattakia through a case study using pushover analysis, and to propose different reinforcement solutions (rehabilitation) for the case and compare them to reduce the damage caused by earthquakes by conducting an applied analytical study on two 3D models of existing buildings. The results of the analysis showed that the reinforcement with the addition of shear walls gave more resistance than the reinforcement with the concrete shirt in terms of mitigating the transitions, while it led to an increase in the base shear.